Effect of water on sandstone's fracture toughness and frictional parameters: Brittle strength constraints. (November 2021) - Noël, Corentin; Baud, Patrick; Violay, Marie
Abstract: Water presence causes a dramatic reduction of sandstone strength. Under compressive stress conditions, the strength of a rock sample is controlled by frictional parameters and the fracture toughness of the material. Here, we report fracture toughness, frictional and uniaxial compression tests performed on five sandstones under dry and water-saturated conditions, that provide new insight into the mechanical influence of water on sandstone strength. The mechanical data show that water saturation causes a reduction of i) the fracture toughness and fracture energy ranging from 6 to 35% and 21–52%, respectively; and ii) the static friction coefficient ranging from 0 to 19%. The results suggest that the water weakening in sandstones (with a reduction of the uniaxial compression strength ranging from 0 to 30%) is due to the reduction of the fracture toughness and of the static friction coefficient of the materials. The measured fracture toughness and frictional parameters are then introduced into two micro-mechanical models (a pore-emanating cracks model and a wing crack model) to predict the water weakening. It is shown that the models predict the water weakening relatively well with a general slight overestimation (10–20%). Finally, a parametric analysis on the wing crack model revealed that a sandstone's absolute strength can be estimated by means of combined physical and mechanical parameter measurements. Key Points: Key point 1: Fracture toughness and friction coefficient are reduced in presence of water. Key point 2: Fracture toughness reduction with water can explain weakening in compressive strength. Key point 3: Micro-mechanical models predict the water weakening well, with slight overestimation.